THE EFFECT OF AFGAN IMMIGRANTS' SOCIOCULTURAL ADAPTATION ON JOB SATISFACTION: THE CASE OF BURSA PROVINCE - Haqyar, Ahmad Jawid; Camgöz, Mevlüt (Uluslararası Mülteci Hakları Derneği, 2023)
The phenomenon of migration comes to the fore as an influential agenda in modern societies as well as in the historical process. In the past, this phenomenon, which was seen as migration from village to city in a national context, has gained an international dimension today. The negative effects of factors such as war and economy have caused the displacement of millions of people. Afghan migration to Turkey since the beginning of the 2000s is one of them. This study aims to reveal the effects of Afghan immigrants' sociocultural adaptation on job satisfaction. Minnesota Job Satisfaction and SCAS-R Sociocultural Adaptation Scales were used in the study. According to the findings, the increase in the sociocultural adaptation level of Afghan immigrants reduces their job satisfaction. The reason for the inverse relationship between the sociocultural adaptation of Afghan immigrants and their job satisfaction is that the expectations and goals of people with high sociocultural adaptation are more difficult to reach and less able to meet their goals compared to the expectations and goals of individuals with low sociocultural adaptation. As the sociocultural adaptation level of Afghan immigrants increases, the decrease in job satisfaction indicates that the immigrant mass will reach a lower level of satisfaction over time. This phenomenon will increase the desire of Afghan immigrants to change jobs and countries.

Göç olgusu tarihsel süreçte olduğu gibi modern toplumlarda da önemli bir gündem maddesi olarak ön plana çıkmaktadır. Geçmişte daha çok ulusal bağlamda köyden kente göç şeklinde görülen bu olgu günümüzde uluslararası bir boyut kazanmış, savaş ve ekonomi gibi faktörlerin olumsuz etkileri milyonlarca insanın yer değiştirmesine sebep olmuştur. 2000’li yılların başından bu yana Türkiye’ye olan Afgan göçü de bunlardan birisidir. Bu araştırma Afgan göçmenlerin sosyokültürel uyumlarının iş tatminine etkilerini ortaya koymayı amaçlamaktadır. Çalışmada Minnesota İş Tatmin ve SCAS-R Sosyokültürel Uyum Ölçekleri kullanılmıştır. Araştırma bulgularına göre Afgan göçmenlerin sosyokültürel uyum düzeylerindeki artış iş tatminini düşürmektedir. Afgan göçmenlerin sosyokültürel uyumu ile iş tatminleri arasında görülen ters yönlü ilişkinin sebebi, sosyokültürel uyumu yüksek kişilerin beklenti ve hedeflerinin sosyokültürel uyumu düşük bireylerin beklenti ve hedeflerine göre ulaşılması daha zor olması ve hedeflerini daha az gerçekleştirebilmeleridir. Afgan göçmenlerin sosyokültürel uyum düzeyi arttıkça iş tatmininin düşmesi göçmen kitlesinin zamanla daha düşük tatmin seviyesine ulaşacağını gösterir. Bu olgu Afgan göçmenlerin iş ve ülke değiştirme isteğini arttıracaktır.
Afgan Göçmenlerin Sosyokültürel Uyumlarının İş Tatminine Etkiler : Bursa İli Örneği
Keywords: Migration; Göç